The aesthetics of violence : art, fiction, drama and film - Appelbaum, Robert, 1952- (Futures of the archive: theory, criticism, crisis., 2017)
Offering an ambitious study of the aesthetics of violence across art, literature, film and theatre, this volume brings together traditional German aesthetic and social theory with the modern problem of violence in art. Written in an engaging style, the book includes examples range from Homer and Shakespeare to slasher films and performance art.